2015
DOI: 10.1073/pnas.1419016112
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial self-assembly of a bacterial hydrophobin

Abstract: The majority of bacteria in the natural environment live within the confines of a biofilm. The Gram-positive bacterium Bacillus subtilis forms biofilms that exhibit a characteristic wrinkled morphology and a highly hydrophobic surface. A critical component in generating these properties is the protein BslA, which forms a coat across the surface of the sessile community. We recently reported the structure of BslA, and noted the presence of a large surfaceexposed hydrophobic patch. Such surface patches are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
134
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(146 citation statements)
references
References 35 publications
10
134
1
1
Order By: Relevance
“…4 Electron microscopic images of the BslA film have demonstrated that the most stable assembly of BslA surface layers correlates with a high degree of order between individual proteins. 12 In our simulations, the outward facing conformation (wt-BslA-L out ) exhibits the most clearly defined upright orientation at the interface in combination with the highest adsorption free energy. The deviation from clearly defined upright orientations we show here for mutant proteins is thus likely to be an important factor in the relative loss of mutant BslA layer stability in vitro, and of the observed wettability of the mutant biofilms in vivo.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…4 Electron microscopic images of the BslA film have demonstrated that the most stable assembly of BslA surface layers correlates with a high degree of order between individual proteins. 12 In our simulations, the outward facing conformation (wt-BslA-L out ) exhibits the most clearly defined upright orientation at the interface in combination with the highest adsorption free energy. The deviation from clearly defined upright orientations we show here for mutant proteins is thus likely to be an important factor in the relative loss of mutant BslA layer stability in vitro, and of the observed wettability of the mutant biofilms in vivo.…”
Section: Discussionmentioning
confidence: 61%
“…4,12 Our simulations provide reliable estimates of the adsorption free energy of wild-type (wt) BslA and enable us to rationalize a number of experimental observations.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The hydrophobicity of the biofilm has been attributed to a small secreted protein named BslA (7,8), which works alongside the fibrous protein TasA (9,10) and the extracellular polysaccharide produced by the products of the epsA-O operon (5) to allow morphogenesis of the biofilm. Partial evidence of the mechanism used by BslA to confer hydrophobicity to the B. subtilis biofilm has been revealed (8,(11)(12)(13). Although transcription of bslA occurs uniformly within the population, secreted BslA is localized to the periphery of the biofilm, where it forms a hydrophobic layer at the airbiofilm surface (8,12).…”
mentioning
confidence: 99%
“…Structural analysis revealed that BslA is an amphipathic protein consisting of an immunoglobin G-like scaffold appended with a hydrophobic "cap" (12) that can present in two forms: "cap in" and "cap out." This property either shields (cap in) or reveals (cap out) the hydrophobic domain in response to the local environment (11). Thus, when BslA is in the aqueous environment of the matrix, it is likely that the hydrophobic cap is "hidden" toward the interior of the protein.…”
mentioning
confidence: 99%